2019
DOI: 10.2196/14366
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Hypothetical Implementation Framework of Expectations for Monitoring Early Signs of Psychosis Relapse Using a Mobile App: Qualitative Study

Abstract: BackgroundRelapse is a common experience for people diagnosed with psychosis, which is associated with increased service costs and profound personal and familial distress. EMPOWER (Early signs Monitoring to Prevent relapse in psychosis and prOmote Well-being, Engagement, and Recovery) is a peer worker–supported digital intervention that aims to enable service users to self-monitor their mental health with the aim of encouraging self-management and the shared use of personal data to promote relapse prevention. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 53 publications
1
37
0
Order By: Relevance
“…Indeed, some studies found a negative correlation between the time spent using eHealth apps and the engagement of patients [ 20 , 21 ]. In addition, many clinicians expressed their concern that if these systems integrate seamlessly with clinical workflow, they will result in an increase in the clinicians’ workload [ 22 , 23 ], which might affect their engagement with the app.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, some studies found a negative correlation between the time spent using eHealth apps and the engagement of patients [ 20 , 21 ]. In addition, many clinicians expressed their concern that if these systems integrate seamlessly with clinical workflow, they will result in an increase in the clinicians’ workload [ 22 , 23 ], which might affect their engagement with the app.…”
Section: Introductionmentioning
confidence: 99%
“…The study methodology also has several strengths. First, multiple stakeholder involvement is considered important for implementation research [ 45 , 47 ]. Thus, conducting focus groups with staff of varying professional groups and patients is a particular strength of the study; a wide selection of viewpoints is likely to be gained.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is likely to fit well with the goals of both staff and patients on wards. Finally, the majority of implementation research is retrospective [ 47 ]. This study benefits from prospectively assessing feasibility of implementation in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of key implementation themes constructed from formative qualitative work conducted before the trial involving 25 focus groups held with mental health staff, carers, and service users across international sites in both the United Kingdom and Australia [47].…”
Section: Methodsmentioning
confidence: 99%
“…Following mapping out key EMPOWER components as described in the protocol (step 1), our formative qualitative work conducted in advance of the trial [47] was key to developing the process evaluation framework (step 2 of our process) and will be described briefly. The person-based approach to intervention evaluation [48] provided a useful guide for structuring the qualitative data as the process evaluation team developed the framework.…”
Section: Methodsmentioning
confidence: 99%